2001
DOI: 10.1002/nau.1001
|View full text |Cite
|
Sign up to set email alerts
|

BPH with coexisting overactive bladder dysfunction—an everyday urological dilemma

Abstract: The aim of this study was to use a systematic schedule, including urodynamics, to describe the rate of coexisting overactive bladder (OB) in patients with bladder outlet obstruction (BOO) caused by benign prostatic hyperplasia (BPH). We also identified differences between the patients with pure BOO compared with those with BOO combined with OB (BOO + OB). One hundred and sixty-two men referred to our clinic due to LUTS were included. Patients with a history that might affect their bladder function were exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 24 publications
2
59
1
3
Order By: Relevance
“…In another study of 100 consecutive patients who underwent TURP, a high proportion of patients reported increasing urine leakage with increasing age [9]. Knutson et al [10] reported that high age was an independent risk factor for coexisting detrusor overactivity in BPE.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 100 consecutive patients who underwent TURP, a high proportion of patients reported increasing urine leakage with increasing age [9]. Knutson et al [10] reported that high age was an independent risk factor for coexisting detrusor overactivity in BPE.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are considered common to most conditions leading to detrusor instability (4). Although there is a strong association among outlet obstruction (17), neurological disease (1), and bladder overactivity, little is known about the events that lead to these changes or the underlying mechanisms involved.…”
mentioning
confidence: 99%
“…Clinically, detrusor overactivity is common in patients with benign prostatic hyperplasia and outfl ow obstruction (11), and Connexin43 expression is increased in patients with neurogenic detrusor overactivity (10). Our present fi ndings suggest that bladder activity is more effectively inhibited by a gap junction blocker after BOO has increased the number of gap junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder outlet obstruction (BOO) caused by benign prostatic hyperplasia in elderly men is associated with detrusor overactivity, which is also the most common cause of overactive bladder syndrome (11). Partial BOO is an established experimental model for producing detrusor overactivity in animals, which causes signifi cant changes of bladder smooth muscle contraction (17).…”
mentioning
confidence: 99%